At the intersection of urbanisation and counterurbanisation in rural space: Microurbanisation in Northern Iceland. (October 2021) - Bjarnason, Thoroddur; Stockdale, Aileen; Shuttleworth, Ian; Eimermann, Marco; Shucksmith, Mark
Abstract: Micropolitan centers and other regional towns have frequently been conceptualised as drivers of economic growth in rural regions, providing an ideal balance between rural and urban amenities. However, they have also been described as "sponges" that suck the population from more rural communities in the region, perhaps only to be squeezed again into the micropolitan bucket of urbanisation. In this paper, we map long-term urbanisation and microurbanisation in Iceland and evaluate the role of micropolitan Akureyri in Northern Iceland in rural migration dynamics. We find the Icelandic rural population to be highly mobile with about nine out of ten residents in different types of communities having lived elsewhere for at least a year, and between a quarter and one-third having lived in the Reykjavík capital area. Positive net in-migration to Akureyri from more rural regions corresponds exactly to negative out-migration towards the Reykjavík capital area and the steady long-term population growth of Akureyri can, thus, be attributed exclusively to natural fertility. However, micropolitan Akureyri does not appear to exacerbate rural out-migration in Northern Iceland. Residents of smaller communities in the north are not more likely to move than other rural residents – they are simply more likely to move to micropolitan Akureyri rather than the Reykjavík capital area. Highlights: The rural population in Iceland is highly mobile. Rural Iceland has seen long-term population growth despite negative net migration. Larger towns have grown while villages and farming communities have declined. Micropolitan growth can be traced to natural fertility and net balance in migration. Micropolitan growth diverts but does not exacerbate rural out-migration.